SOSIALISASI PERSIAPAN PENATAAN WISATA DALAM UPAYA MERINTIS DESA WISATA DI BUKIT SUMINGKIR - Tsuroya, Alihfa Hasna; Zalzabila, Adinda; Saiful Millah, Muhammad; Novitasari, Nastiti (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Community service through this socialization activity is carried out in an effort to empower the community of Rajadatu Village through socialization activities in preparation for the development of Bukit Sumingkir tourist area. The goal of this community service is to enhance active participation of the community in the development and arrangement of local tourist destinations. The community service method involves a participatory approach and socialization activities to improve the community's understanding of the arrangement of the tourist area. The results of the community service show an increase in community involvement, understanding of the benefits of arranging the tourist area, and the potential for local economic development. The implication of this community service underscores the importance of collaborative efforts between the government and the community in pioneering and developing the tourism potential to achieve sustainable development at the village level.